Influence of Financial Ratios and Good Corporate Governance on Financial Performance - Manap, Abdul; Br Ginting, Riah Ukur; Sasmiyati, Rini Yulia; Pane, Saut; Pujadi, Arko (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine and analyze the influence of profitability, liquidity, and good corporate governance on the financial performance of Food and Beverage sector companies listed on the Indonesia Stock Exchange during the 2020–2024 observation period. The research applies a purposive sampling technique to select companies that meet predetermined criteria that are relevant to the research objectives, resulting in a total sample of 14 companies with 70 annual report observations for five consecutive years. The data analysis method used in this study is multiple linear regression, supported by descriptive statistical analysis, classical assumption testing, and hypothesis testing to ensure the reliability and validity of the findings. The results of the study show that profitability has a positive and significant effect on financial performance, meaning that companies with higher profitability ratios tend to achieve better financial outcomes. However, liquidity and institutional ownership as part of good corporate governance do not have a significant effect on financial performance, indicating that they may not directly influence a firm’s ability to generate returns in this industry context. These findings emphasize that profitability is one of the most dominant internal factors in determining financial success, while liquidity and institutional ownership have a limited role. Overall, the study contributes to strengthening empirical evidence regarding the role of financial management and governance practices in shaping company performance in the Indonesian Food and Beverage industry.